1997
DOI: 10.1163/156856897x00177
|View full text |Cite
|
Sign up to set email alerts
|

Fixation sequences made during visual examination of briefly presented 2D images

Abstract: Eye movements made by eighteen observers in response to brief (3 s) presentations of eleven different images, each in three forms (unfiltered, high-pass filtered and low-pass filtered), have been analysed in order to identify both repeated sequences of fixations and image locations which attract re-fixations. It is shown that eye-movement traces made by different observers in response to the same image have few common temporal sequences involving the same fixation locations, even for sequences of only two fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 0 publications
2
74
0
Order By: Relevance
“…Image statistics of areas selected for eye fixation within scenes differ in systematic ways from areas that are not fixated. A possible interpretation of these results is that fixation position can be accounted for by low-level image statistics (Krieger et al, 2000;Mannan et al, 1995Mannan et al, , 1996Mannan et al, , 1997aParkhust & Niebur, 2003;Reinagel & Zador, 1999). The present results, however, call this interpretation into question.…”
Section: Analysis 3: Are Fixated Scene Regions More Semantically Infomentioning
confidence: 53%
See 1 more Smart Citation
“…Image statistics of areas selected for eye fixation within scenes differ in systematic ways from areas that are not fixated. A possible interpretation of these results is that fixation position can be accounted for by low-level image statistics (Krieger et al, 2000;Mannan et al, 1995Mannan et al, , 1996Mannan et al, , 1997aParkhust & Niebur, 2003;Reinagel & Zador, 1999). The present results, however, call this interpretation into question.…”
Section: Analysis 3: Are Fixated Scene Regions More Semantically Infomentioning
confidence: 53%
“…Several studies have demonstrated that the image properties of fixated regions tend to differ in systematic ways from regions that are not fixated (Krieger et al, 2000;Mannan, et al, 1995Mannan, et al, , 1996Mannan, Ruddock, & Wooding, 1997a;Parkhurst & Niebur, 2003;Reinagel & Zador, 1999). Specifically, fixated scene regions tend to be lower in intensity but higher in edge density and local contrast, and are more likely to contain third-order spatial relationships such as T-junctions and curves, than non-fixated regions.…”
Section: Analysis 2: Measuring Local Image Statistics At Fixated Locamentioning
confidence: 99%
“…These algorithms compare two scanpaths by computing how long various locations are looked at, how far each fixation point in one scanpath is from the closest fixation point in the other scanpath, and so forth. One of the earliest algorithms based on attention measures is the Mannan distance algorithm (Mannan, Ruddock, & Wooding, 1997). However, this class of scanpath-comparison techniques has a number of drawbacks-most importantly for our purposes, the temporal order of fixations is lost.…”
Section: Attention Map (Amap) Scanpath Comparisonmentioning
confidence: 99%
“…Refixations are operationally defined as a shift in gaze back to the target object before the scene-terminating intervening-object criterion was achieved. We isolated and analyzed those trials in which observers made at least one target refixation and found an overall refixation rate of 35%, a rate somewhat higher than is typically found in visual search or picture viewing tasks (Dickinson & Zelinsky, 2005;Mannan et al, 1997). This refixation rate also varied with intervening-object condition.…”
Section: Resultsmentioning
confidence: 96%
“…Refixations are a ubiquitous property of normal gaze behavior and have been noted in tasks as diverse as reading (Rayner, 1978(Rayner, , 1998, pattern copying or block sorting (Ballard, Hayhoe, & Pelz, 1995;Droll & Hayhoe, 2007;Hayhoe, Bensinger, & Ballard, 1998), portrait painting (Locher, 1996;Nodine, Locher, & Krupinski, 1993), solving arithmetic and geometry problems (Epelboim & Suppes, 1996;Hegarty, Mayer, & Green, 1992), visual search (Gilchrist & Harvey, 2000;Peterson, Kramer, Wang, Irwin, & McCarley, 2001), and undirected picture viewing (Mannan, Ruddock, & Wooding, 1996, 1997. Refixations can also comprise a significant portion of the gaze behavior accompanying a task-by one estimate, up to 25% of the observed fixations (Mannan et al, 1997).…”
mentioning
confidence: 99%